Pengaruh Pendekatan Contextual Teaching and Learning Berbantuan Media Papan Pintar Terhadap Pemahaman Konsep Matematis Siswa Sekolah Dasar - Amalia Muthia; Sofyan Iskandar; Teten Ginanjar Rahayu (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to analyze the effect of the Contextual Teaching and Learning (CTL) model, supported by smart board media, on elementary school students’ understanding of mathematical concepts regarding the place value of natural numbers from 1 to 1,000. The research method used was a quasi-experimental study with a non-equivalent control group design. The research sample consisted of 54 third-grade students at SDN 2 Nagrikaler, divided into an experimental class and a control class. The instrument used was a mathematical concept comprehension essay test that had been validated for validity and reliability. Data analysis techniques included prerequisite tests, simple linear regression, the coefficient of determination, the paired-sample t-test, and the independent-sample t-test. The results of the study indicate that Contextual Teaching and Learning (CTL) supported by smart board media has a significant effect on students’ understanding of mathematical concept , contributing 55.6%. Thus, the integration of the CTL model and smart board media is effective in improving mathematical concept understanding in elementary school.